Elastic Fluctuations and Structural Heterogeneities in Metallic Glasses. (27th May 2018) - Liu, Chaoyang; Maaß, Robert
Abstract: Suppressing crystallization of a metallic melt results in a disordered solid, also known as a metallic glass. One may conclude that a metallic glass is free of defined structural length scales beyond some atomic‐scale value that characterizes short‐ and medium‐range order. While it is well known from atomistic modeling that a metallic glass is structurally heterogeneous, heterogeneities at such a small length scale can hardly be resolved in experiments. This review highlights experimental insights into elastic fluctuations and structural heterogeneities that emerge at scales between a few nanometers and tens to hundreds of micrometers. It distinguishes between structural and property fluctuations in as‐cast metallic glasses, and heterogeneities introduced by elastic and inhomogeneous plastic deformation. As‐cast glasses reveal elastic fluctuations across 3 orders of magnitude, suggesting a hierarchy of length scales that can be tuned by thermomechanical processing. Similarly, nanoscale strain localization into shear bands drives the formation of structural and elastic heterogeneities at both the nano‐ and the microscale. It is proposed that both types of fluctuations will allow one to quantitatively define structure–property relationships via measurable length scales—an approach that has largely contributed to the engineering success of crystalline metals. Abstract : Relating microstructure with macroscopic materials properties is a foundational principle in materials science, which is very challenging for metallic glasses. This review summarizes recent experimental progress on the quantitative characterization of internal length scales in metallic glasses. It highlights elastic and structural fluctuations which may allow us to formulate novel structure‐property relationships for metallic glasses.